Wheat farmers in Sudan record increased yields after adoption of proven technologies: TAAT news Vol. 1 - Technologies for African Agricultural Transformation (Technologies for African Agricultural Transformation, 2019)
The technologies for African Agricultural Transformation (TAAT) Program was initiated by the African Development Bank (AfDB) as a flagship program of its Feed Africa Initiative. The development objective of TAAT is to rapidly expand access of smallholder farmers, majority women, to high-yielding agricultural technologies to improve their food production, assure food security and raise rural incomes, and deliver regional public goods by scaling up agricultural technologies across similar agro-ecological zones.